"It's a Marathon, Not a Sprint": The Implementation and Outcomes of a Yearlong Racial Justice Intervention - Adriana Villavicencio; Sarah Klevan; Dana Conlin; Kathryn Hill (SAGE Publishing, 2022)
Although scholarship documenting the effects of racism on educational outcomes is extensive, less empirical research has been done on interventions designed to mitigate racism and racial bias in schools. Based on case studies of two elementary schools, we have found that educators participating in a yearlong racial justice program demonstrated a deeper understanding of their own racial biases, developed a shared language to identify and name different forms of racism, and reported greater confidence to disrupt racist incidents in their schools. In one site, however, inconsistent leadership and resistance from a vocal White minority limited the program's potential to change schoolwide practice. In the other site, educators reported changes in curricular materials and changes to disciplinary decisions, but widespread organizational change will likely take longer than a single school year. Drawing on these findings, we discuss implications for anti-racist interventions in other educational contexts as well as recommendations for studying their efficacy.